Self‐promotion Statements in Video Resumes: Frequency, intensity, and gender effects on job applicant evaluation. (December 2015) - Waung, Marie; Hymes, Robert; Beatty, Joy E.; McAuslan, Pam
Abstract : Although video resumes have received a substantial amount of media attention and there seems to be a growing awareness among Human Resource professionals of video‐based job applications, little is known about the effect of video resumes on applicant evaluation. This research investigates the effectiveness of self‐promotion within the context of video resumes. Self‐promotion frequency and intensity and applicant gender were manipulated. Ratings by recruiters and college students indicate that high levels of self‐promotion in video resumes are ineffective for male applicants and potentially detrimental for female applicants. Job applicants should use caution when attempting to promote themselves using video resumes. More research is needed on impression management tactics used at the earliest stages of selection and on the mechanisms operating within video resumes that impact applicant evaluation.